2010
DOI: 10.1051/forest/2009089
|View full text |Cite
|
Sign up to set email alerts
|

Le chaulage forestier influence durablement les communautés d’ectomycorrhizes et de carpophores épigés

Abstract: Abstract• Liming is a forestry practice used to counteract forest decline in acidic soils. It consists of direct Ca and Mg input to forest soil, which restores tree mineral nutrition, but also modifies microbial communities in soil. The aim of this study was to assess the effects of liming on both belowground (ectomycorrhizal root tips) and aboveground (epigeous sporocarps) fungal communities.• Results showed that the modification of soil chemical properties (pH, and Ca-Mg contents versus total free Al and Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Rineau et al (2010) found that tree host was a stronger factor of community structuring than soil chemical changes associated with liming. Several studies have demonstrated that the composition of fungal communities changes during the forest succession (Hintikka 1988;Last et al 1987;Dighton et al 1986).…”
Section: Impact Of Atmospheric Input Of Nitrogenmentioning
confidence: 95%
“…Rineau et al (2010) found that tree host was a stronger factor of community structuring than soil chemical changes associated with liming. Several studies have demonstrated that the composition of fungal communities changes during the forest succession (Hintikka 1988;Last et al 1987;Dighton et al 1986).…”
Section: Impact Of Atmospheric Input Of Nitrogenmentioning
confidence: 95%
“…It has also strongly enhanced colonization by earthworms as shown by the abundance of mounds. The present soil chemical properties in the treated and untreated plots have been published previously (Rineau et al 2010). …”
Section: Forest Standmentioning
confidence: 99%
“…The limestone-rich soils of the analyzed sites developed on permocarbon deposits account for the presence of ECM A. byssoides, which is known to increase in abundance after liming of otherwise acidic sites in pine forests (Veerkamp et al, 1997). However, Russula and Lactarius spp, cosmopolitan and widespread in the northern hemisphere (Dickie and Moyersoen, 2008), particularly at more acidic sites (Rineau et al, 2010), were not present in ECM P. crassifolia. A general lack of ECM Russula and Lactarius spp at the sites suggests that a combination of environmental conditions, such as the distinct soil conditions and low precipitation in the Helan Mountains, influences and reduces the presence of ECM organisms.…”
Section: Discussionmentioning
confidence: 95%